Improving Students’ Understanding of Animals’ Movement Organs through VideoScribe-based Learning - I Kadek Sukadana; I Gusti Ngurah Japa (Jurnal Ilmiah Sekolah Dasar, 2021)
Teachers do not apply interesting learning models that can stimulate students in learning. In addition, the lack of learning media that can facilitate students in learning has an impact on students' low science learning outcomes. This study aims to develop a learning video about Animal Movement Organs to improve students' understanding in learning. This type of research is development research. The model used to develop the product is ADDIE. Techniques that collect data are interviews and questionnaires. The instrument used to collect data is a questionnaire. The subjects of this study amounted to 4 experts. The analysis technique in this research is descriptive qualitative statistical analysis and descriptive quantitative. The results of the research are the test results from the content experts of the developed media subjects get a value of 4.71 (very good), the test results from the learning media experts get a value of 4.75 (very good) and the results of the validity test of the developed media teachers get a value of 4 .83 (very good). It can be concluded that the learning video media regarding animal movement organs based on video scribe is feasible to be applied in learning. The implication of this research is that the developed media can make it easier for students to understand the material of animal movement organs and can facilitate students in independent learning.